Analysis of hate speech as a form of discrimination: concepts, criteria and structure - Miguel Bastías Quezada (Revista de Derecho)
The purpose of this paper is to study hate speech, based on the  distinction  between  hate  speech  and discrimination. See how international jurisprudence has opted for more liberal or restrictive conceptions in this matter. Afterwards, the regulation of hate speech in our country will be analyzed, making reference to the current norms and bills in process. Finally, an analysis of the structure of hate speech will be made, of the criteria that should be considered to evaluate a discourse, and how hate speech proper, constitutes a limitation to freedom of speech.